Endothelial APC/PAR1 distinctly regulates cytokine-induced pro-inflammatory VCAM-1 expression - Birch, Cierra A.; Wedegaertner, Helen; Orduña-Castillo, Lennis B.; Gonzalez Ramirez, Monica L.; Qin, Huaping; Trejo, JoAnn (Frontiers in Molecular Biosciences, 2023)
Introduction: Dysfunction of the endothelium impairs its’ protective role and promotes inflammation and progression of vascular diseases. Activated Protein C (APC) elicits endothelial cytoprotective responses including barrier stabilization, anti-inflammatory and anti-apoptotic responses through the activation of the G protein-coupled receptor (GPCR) protease-activated receptor-1 (PAR1) and is a promising therapeutic. Despite recent advancements in developing new Activated protein C variants with clinical potential, the mechanism by which APC/PAR1 promotes different cytoprotective responses remains unclear and is important to understand to advance Activated protein C and new targets as future therapeutics. Here we examined the mechanisms by which APC/PAR1 attenuates cytokine-induced pro-inflammatory vascular cell adhesion molecule (VCAM-1) expression, a key mediator of endothelial inflammatory responses. Methods: Quantitative multiplexed mass spectrometry analysis of Activated protein C treated endothelial cells, endothelial cell transcriptomics database (EndoDB) online repository queries, biochemical measurements of protein expression, quantitative real-time polymerase chain reaction (RT-qPCR) measurement of mRNA transcript abundance, pharmacological inhibitors and siRNA transfections of human cultured endothelial cells. Results: Here we report that Activated Protein C modulates phosphorylation of tumor necrosis factor (TNF)-α signaling pathway components and attenuates of TNF-α induced VCAM-1 expression independent of mRNA stability. Unexpectedly, we found a critical role for the G protein-coupled receptor co-receptor sphingosine-1 phosphate receptor-1 (S1PR1) and the G protein receptor kinase-2 (GRK2) in mediating APC/PAR1 anti-inflammatory responses in endothelial cells. Discussion: This study provides new knowledge of the mechanisms by which different APC/PAR1 cytoprotective responses are mediated through discrete β-arrestin-2-driven signaling pathways modulated by specific G protein-coupled receptor co-receptors and GRKs.